2013
DOI: 10.1007/s00436-013-3289-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the acaricidal activity of carvacrol, (E)-cinnamaldehyde, trans-anethole, and linalool on larvae of Rhipicephalus microplus and Dermacentor nitens (Acari: Ixodidae)

Abstract: The acaricidal activity of carvacrol, (E)-cinnamaldehyde, trans-anethole, and linalool was studied on Rhipicephalus microplus and Dermacentor nitens larvae. All the substances were tested at concentrations of 2.5, 5.0, 10.0, 15.0, and 20.0 μl/ml, with 10 repetitions per treatment. The modified larval packet technique was employed in the tests and the mortality was evaluated after 24 h. In the groups treated with carvacrol, the lowest concentration (2.5 μl/ml) was sufficient to cause 100% death of the R. microp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(13 citation statements)
references
References 35 publications
1
10
0
2
Order By: Relevance
“…Trans-anethole showed the best larvicidal effect as evidenced by the lowest concentration (0.56%) required to attain the LC50 meanwhile, fenchone showed weakest larvicidal effect as its LC50 reached at a concentration of 9.11%. Our results come in accordance with de Oliveira Souza Senra et al [ 41 ] as they found that the treatment with the highest concentrations of fennel oil (20.0 μl/ml) caused 100% mortality in the larvae of R . microplus and D .…”
Section: Discussionsupporting
confidence: 92%
“…Trans-anethole showed the best larvicidal effect as evidenced by the lowest concentration (0.56%) required to attain the LC50 meanwhile, fenchone showed weakest larvicidal effect as its LC50 reached at a concentration of 9.11%. Our results come in accordance with de Oliveira Souza Senra et al [ 41 ] as they found that the treatment with the highest concentrations of fennel oil (20.0 μl/ml) caused 100% mortality in the larvae of R . microplus and D .…”
Section: Discussionsupporting
confidence: 92%
“…Treatment with carvacrol (2.5 μL/mL) induced 100% death of larvae of the cattle parasite Rhipicephalus microplus and the tropical horse tick parasite Dermacentor nitens , suggesting the potential of the monoterpene to control these two tick species in the field . A related study on the acaricidal efficacy of carvacrol and related compounds on larvae of nymphs of Amblyomma cajennense (Cayenne tick) and Rhipicephalus sanguineous parasites that afflict horses and other animals found that similar low concentrations of carvacrol and thymol (2.5 μL/mL) also cause 100% lethality in these parasites, indicating the value of further studies to evaluate these acaricides under natural conditions …”
Section: Inhibition Of Human Pathogenic Bacteriamentioning
confidence: 99%
“…Likewise, ( E )-cinnamaldehyde was effective with 100% mortality at a concentration of 5 μL/mL against R . microplus and Dermacentor nitens larvae [ 38 ]. Acaricidal activity of ( E )-cinnamaldehyde was also observed against the larvae of Amblyomma sculptum (LC 50 1.40 mg/mL) and D .…”
Section: Resultsmentioning
confidence: 99%